Arabic Grammar Educational System (AGES) - Mohammad Injadat, Mohammad Noor Ahmad (2001)
In last few years, the computer technologies developed in dramatically At the same time new high-level languages appeared, and multimedia development all of these factors take out new applications to appear and solve our real life problems One of these languages is Visual Basic, which uses the visual environment to design and fun our systems, which make the programming easier and application's Interface more attractive to the user and developers, In addition to possibility of using multimedia tools in the applications One category of these visualized applications IS educational systems, which been recommended in high degree from the educational crew more than unvisualized applications There is a lot of educational systems that already appeared and used by global but unfortunately rare of these system devoted to learning Arabic Language to non Arabian students. specially in Arabic Grammar, which is difficult to understand. Because all of these factors I'm going to develop an educational application that will give any non Arabian student. who studying Arabic language in advanced level one of the most important lessons in Arabic grammar by discussing the topic in details with an examples, and at the last the system will examine the student by multiple choice exam, and after the student finish his exam the student will be given his result from the system. The system will be developed Using Visual Basic 6, by using the language tools and features. such as multimedia tools. Visual Basic scripts.